"Análise da iluminação natural em ambiente de ensino em relação ao conforto visual e ciclo circadiano" - BARBARA LUDMILLA DAS NEVES DE QUEIROZ (2024)
Nowadays, human beings spend more and more time indoors, resulting in greater exposure to artificial light compared to natural light. This scenario can have adverse effects, since interaction with natural light plays an important role in regulating the circadian cycle, relieving tension, and also has bactericidal and germicidal properties, as well as providing a more pleasant and dynamic sensation. Recent studies have made it possible to calculate the quantity and quality of properties related to lighting and the circadian cycle, such as: the M/P (Melanopic/Photopic) ratio, the Equivalent Melanopic Lux (EML) and the illuminances required for visual comfort and work plan. The purpose of this study was to assess the quality of natural lighting in classrooms in the city of Campo Grande - MS, considering the circadian cycle. To this end, the methodology used was to simulate classrooms based on the FNDE standards, in which the models differed in terms of the material of the openings and their orientation. The classroom was modeled using the Rhinoceros 7 program and simulated using the Alfa plugin. The results were obtained by analyzing several variables such as: openings with different glazing, different orientations, different days (June 21, September 21 and December 21) and times (9 a.m., 11 a.m., 2 p.m. and 4 p.m.), with cloudy and clear skies for the city of Campo Grande - MS. After analyzing the results obtained by the ALFA plugin, a methodology was developed in order to find which classroom model was closest to the ideal model proposed. From the results, it can be seen that the change of glass in the model with South orientation was had the worst result, while the same model with different glazing had the best result considering 150 lux ≤ EML ≤ 3000 lux. This result highlighted the importance of evaluating the material used and how it can affect the project. The analysis of the current model of openings and their performance in classrooms according to visual comfort and the circadian cycle, serves as an initial step towards rethinking the way we design openings and internal lighting in classrooms.